Performance Analysis of OTDM System at the Different Data Rate (International Journal of Engineering and Computer Science, 2015)
OTDM is an updating technique to TDM that provides high speed data generation. It is a technique which overcomes the bandwidth limitation of electronics. The basic principle of this technology is to multiplex number of low bit rate optical channels in time domain. In this paper, the performance of OTDM system is analysed at different data rates i.e.40 Gbps, 80 Gbps and 160 Gbps respectively. The single mode fiber with dispersion 17.65 ps/ nm-km is used. The maximum transmission length achieved is 145km for 40Gbps OTDM system with Q-factor of 29.22 and BER of